Digital Government Transformation thru the Electronification of Regional Government Transactions in Optimizing Land and Building Tax Revenue in Jambi City 2023 - Sintia, Fenny; Beriansyah, Alva; Maulana, Rio Yusri (LPPM Universitas Jambi, 2026)
This research aims to analyze in depth the process of digital government transformation through the implementation of Regional Government Transaction Electrification (ETPD) based on the Quick Response Code Indonesian Standard (QRIS) to optimize Land and Building Tax revenue in Jambi City. This research uses a qualitative case study approach. The data collection techniques for this research are interviews and documentation. The findings of this study explain that the digital transformation of Land and Building Tax (PBB) payments through the implementation of QRIS at the BPPRD of Jambi City is part of the implementation of the Regional Government Transaction Electrification Policy (ETPD), driven by national regulations and the local government's commitment to supporting cashless transactions. The digital transformation of land and building tax (PBB) payments in Jambi City is still at the stage of digitalization, which means the utilization of technology to support existing processes, and has not yet reached the stage of digital transformation characterized by comprehensive structural, cultural, and behavioral changes. Therefore, the digital transformation underway can be characterized as a partial, gradual transformation, which requires strengthening socialization strategies, improving the community's digital literacy, and optimizing incentive policies to achieve digitization goals more effectively.